Faktor-faktor Yang Mempengaruhi Pilihan Metode Depresiasi Di Perusahaan: Studi Kasus Pada Sektor Manufaktur - Denny, Recka; Adriansyah, Adriansyah (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
This research aims to identify the factors influencing the choice of depreciation methods in manufacturing companies in Indonesia. The selection of depreciation methods has a significant impact on financial statements, company performance, and stakeholder perceptions. Using a qualitative approach, this research analyzes the factors influencing the decisions of manufacturing companies in Indonesia in choosing depreciation methods. Through case studies, the research findings are expected to provide valuable insights for researchers and encourage the application and development of knowledge gained during the lecture period. The findings indicate that most manufacturing companies in Indonesia use the straight-line method to calculate the depreciation of their fixed assets, with the main factors influencing the choice of depreciation method being the type and age of the assets, as well as tax considerations.